Hemoglobin extravasation in the brain of rats exchange-transfused with hemoglobin-based oxygen carriers. (19th May 2017) - Terraneo, Laura; Bianciardi, Paola; Malavalli, Ashok; Mkrtchyan, Gnel; Spann, Stephanie N.; Lohman, Jeff; Samaja, Michele; Vandegriff, Kim D.
Abstract: Haemoglobin (Hb)-based oxygen carriers are under consideration as oxygen therapeutics. Their effect on apoptosis is critical, because the onset of pro-apoptotic pathways may lead to tissue damage. MP4OX, a polyethylene glycol-conjugated human Hb preserves the baseline level of neuron apoptosis with respect to sham. Here we develop a method for measuring Hb extravasation in brain. We exchange transfused rats by haemorrhaging 50% of their blood with simultaneous, isovolemic replacement with Hextend (negative control), MP4OX, or αα-cross-linked Hb. Animals were sacrificed 2 h after transfusion, brain tissue was harvested and processed for double-staining immunofluorescence, whereby Hb ? chain and NeuN (a neuron protein) were stained and quantitated. Whereas Hextend did not induce Hb extravasation, in both MP4OX and ??Hb brains Hb molecules were detected outside neurons. The level of extravasated Hb chains was > 3-fold higher in Hb compared to MP4OX. Western blot analysis revealed that the expression levels of protein related to redox imbalance (e.g., Nrf2, iNOS and ERK phosphorylation) were higher in ααHb than MP4OX. In conclusions, higher Hb extravasation in ααHb than MP4OX induces redox imbalance, which causes higher anti-oxidant response. Whereas Nrf2 response may be considered protective, iNOS response appears damaging.